2020
DOI: 10.1101/2020.03.05.978841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The paradoxical effects of K+channel gain-of-function are mediated by GABAergic neuron hypoexcitability and hyperconnectivity

Abstract: Gain-of-function (GOF) variants in K + channels cause severe childhood epilepsies, but there are no mechanisms to explain how increased K + currents lead to network hyperexcitability. Here, we introduced a human Na + -activated K + (KNa) channel variant (KCNT1-Y796H) into mice and, using a multiplatform approach, found motor cortex hyperexcitability and early-onset seizures, phenotypes strikingly similar to those of human patients. Although the variant increased KNa currents in cortical excitatory and inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Recently, data supporting the mechanism that gain-of-function Slack mutations, such as A934T, lead to epilepsy through inhibitory neuron-mediated mechanisms by prolonging afterhyperpolari-zation and increasing currents at subthreshold voltages. 24 Indeed, we found that our synchronously firing neuronal cultures contained a mixture of inhibitory and excitatory neurons as well as astrocytes (Figure S5, Supporting Information), and it is tempting to speculate that the decrease in spike rate observed when neurons were treated with VU0606170 resulted from increasing inhibitory tone. Additionally, we were encouraged by the face that application of VU0606170 decreased the spike rate but did not completely suppress neuronal activity.…”
Section: ■ Conclusionmentioning
confidence: 94%
See 4 more Smart Citations
“…Recently, data supporting the mechanism that gain-of-function Slack mutations, such as A934T, lead to epilepsy through inhibitory neuron-mediated mechanisms by prolonging afterhyperpolari-zation and increasing currents at subthreshold voltages. 24 Indeed, we found that our synchronously firing neuronal cultures contained a mixture of inhibitory and excitatory neurons as well as astrocytes (Figure S5, Supporting Information), and it is tempting to speculate that the decrease in spike rate observed when neurons were treated with VU0606170 resulted from increasing inhibitory tone. Additionally, we were encouraged by the face that application of VU0606170 decreased the spike rate but did not completely suppress neuronal activity.…”
Section: ■ Conclusionmentioning
confidence: 94%
“…One proposed mechanism by which mutant Slack channels cause seizures is by enhancing K + currents in GABAergic neurons . This increase in current, especially in nonfast spiking GABAergic neurons, leads to prolonged hyperpolarization, resulting in a decrease in inhibitory interneuron activity and an overall decrease in inhibitory tone. ,, Second, this reduced excitability has been accompanied by an increase in excitatory–excitatory and inhibitory–inhibitory synaptic connectivity . It is thought that this increase in synaptic connectivity early in development predisposes the nervous system to develop circuits that generate epileptic discharges. , The resulting overall imbalance between neuronal excitation and inhibition leads to the development of seizures. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations